Discussion on Strengthening Collaborative Supervision and Deepening the Construction of a Clean and Honest University - Zhang, Linzi (Journal of Educational Research and Policies, 2025)
County made strategic arrangements for improving the supervision system under the unified leadership of the Party, with full coverage and authoritative and efficient operation. As one of the most important supervisory institutions, the theoretical discussion on the convergence and coordination of various types of supervision in colleges and universities is still very limited. This paper analyzes the problems and causes encountered by colleges and universities in the joint supervision force in recent years. With internal supervision as the leading factor and the convergence and coordination of various types of supervision as the train of thought, it explores how to effectively utilize collaborative and linkage measures to improve the efficiency of regular management of supervision in colleges and universities, in the hope of providing references for other colleges and universities to explore the joint supervision force and promote the convergence and coordination of various types of supervision.